A SARS-CoV-2 nucleocapsid ELISA represents a low-cost alternative to lateral flow testing for community screening in LMI countries. Issue 1 (January 2022) - Humbert, Maria Victoria; Opurum, Precious Chinonyerem; Brendish, Nathan J; Poole, Stephen; He, Peijun; Katis, Ioannis; Quaye, Jerry; Bediako, Yaw; Duriez, Patrick Jacques; Eason, Robert W; Sones, Collin; Quaye, Osbourne; et al.
Highlights: Low-cost SARS-CoV-2 nucleocapsid ELISA with limit of detection of 8.4 pg/ml. Sensitivity of 78 and 72% in UK and Ghana trials for samples with ct values ≤ 30. Specificity of 100% in both UK and Ghana trials. Correlation between nucleocapsid and RNA levels in samples but occasional outliers. Summary: Background Controlling the spread of SARS-CoV-2 is problematic because of transmission driven by asymptomatic and pre-symptomatic individuals. Community screening can help identify these individuals but is often too expensive for countries with limited health care resources. Low-cost ELISA assays may address this problem, but their use has not yet been widely reported. Methods We developed a SARS-CoV-2 nucleocapsid ELISA and assessed its diagnostic performance on nose and throat swab samples from UK hospitalised patients and sputum samples from patients in Ghana. Results The ELISA had a limit of detection of 8.4 pg/ml antigen and 16 pfu/ml virus. When tested on UK samples (128 positive and 10 negative patients), sensitivity was 58.6% (49.6–67.2) rising to 78.3% (66.7–87.3) if real-time PCR Ct values > 30 were excluded, while specificity was 100% (69.2–100). In a second trial using the Ghanaian samples (121 positive, 96 negative), sensitivity was 52% (42.8–61.2) rising to 72.6% (61.8–81.2) when a  > 30 Ct cut-off was applied, while specificity was 100% (96.2–100). Conclusions: Our data show that nucleocapsid ELISAs can test a variety of patient sample types while achieving levels of sensitivity and specificity required for effective community screening. Further investigations into the opportunities that this provides are warranted.